1992
DOI: 10.1128/iai.60.1.237-248.1992
|View full text |Cite
|
Sign up to set email alerts
|

Shigella flexneri enters human colonic Caco-2 epithelial cells through the basolateral pole

Abstract: The commonly accepted view that enteroinvasive bacteria enter cells of the intestinal epithelial lining through the apical surface can be challenged in the case of shigellosis. This study is based on in vitro experiments that showed that the invasion of human colonic Caco-2 cells by Shigella flexneri occurred through the basolateral pole of these cells. In these experiments, the few bacteria that interacted with the apical surface either bound to microvilli of the cell dome without causing detectable alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(163 citation statements)
references
References 37 publications
10
152
0
1
Order By: Relevance
“…Moreover, microscopic observations of noncon£uent monolayers revealed that bacteria adhered mainly to the outer edge of peripheral cells of the islets. This pattern of adherence resembled that of some enteroinvasive bacteria that enter through the basolateral surface of di¡erentiated and nondi¡erentiated polarized Caco-2 cells [4,5].…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, microscopic observations of noncon£uent monolayers revealed that bacteria adhered mainly to the outer edge of peripheral cells of the islets. This pattern of adherence resembled that of some enteroinvasive bacteria that enter through the basolateral surface of di¡erentiated and nondi¡erentiated polarized Caco-2 cells [4,5].…”
Section: Discussionmentioning
confidence: 60%
“…and S. enterica. Shigella cannot invade epithelia from the apical side and the current model proposes that Shigella has to be transcytosed through M cells to be able to invade epithelial cells from the basolateral side by a mechanism that is similar to the SPI1-mediated invasion of Salmonella (Mounier et al, 1992;Nhieu and Sansonetti, 1999). As the invasion of M cells has also been reported for Salmonella (Jones et al, 1994), basolateral invasion of epithelial cells might also be deployed by Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showing in vitro that asp, integrin, the receptor for Yersinia invasin, which plays a primary role in the initiation of infection 1391, does not appear accessible for cell infection after the Caco-2 cells commence their differentiation or are fully differentiated, explain why Yersinia species cannot invade differentiated intestinal epithelial cells in vivo. Other enteroinvasive bacteria, such as Lisreria monocytogenes [ 12, 131 and Shigella j k x n e r i [34], can promote infection of undifferentiated Caco-2 cells and cannot enter the apical side of polarized differentiated Caco-2 cells. For S. j k x n e r i , the cell adhesion molecule L-CAM is required for cell-to-cell spread [34, 451. In contrast to s. ,flexnevi and I: pseudotuberculosis, we have observed that neither aJ3, integrins nor E-cadherin is involved in infection of undifferentiated Caco-2 cells by L. monocytogenes (M.-H. Coconnier, personal communication).…”
Section: Discussionmentioning
confidence: 99%